Türkiye’de Telekomünikasyon Sektöründe Kurumsal İtibar Katsayısı ve Marka Sadakati Üzerine Bir Araştırma - KARAYEL BİLBİL, EMEL; SÜTCÜ, CEM SEFA (My University, 2013)
Bu çalışmada, Türkiye’deki telekomünikasyon sektöründe hizmet veren kurumların paydaşlarının kurumsal itibara bakışları ve marka sadakati ilişkisi incelenmiştir. Telekomünikasyon sektöründe faaliyet gösteren dört firma üzerine, niceleyici çalışma yapılmıştır. Kurumsal itibar katsayısını oluşturan boyutlar incelenmiş ve ağırlıkları tespit edilmiştir. Ayrıca kurumsal itibar katsayısı ile marka sadakati arası ilişki incelenmiştir. Fombrun’un RQ modeli altı boyutta incelenirken, Türkiye’deki telekomünikasyon sektöründe bu altı boyutun, iki boyut altında toplandığı görülmüştür. Turkcell, kurum itibarı katsayısı en yüksek olan firma olarak çıkmıştır. Marka sadakati ile kurumsal itibar katsayısı arası ilişki olduğu görülmüştür. Anahtar Kelimler: Kurumsal İtibar Katsayısı, Marka Sadakati

In this paper, stakeholder views to the corporate reputation in relation to brand loyalty were studied among the corporations operating in Turkish telecommunications sector. Quantitative analyses were conducted on four firms operating in telecommunications sector. Dimensions constituting the Corporate Reputation Quotient were inspected and their weights assessed. Besides, the relation between Corporate Reputation Quotient and Brand Loyalty was examined. While Fombrun’s RQ model is examined in six dimensions, it revealed that these six dimensions were grouped into two in Turkish telecommunications sector. Turkcell, has been found, among others, as the firm with the highest Corporate Reputation Quotient. It was also found that there is a relation between Brand Loyalty and Corporate Reputation Quotient. Keywords: Corporate Reputation Quotient, Brand Loyalty
Research on corporate reputation quotient and brand loyality in telecommunications sector in turkey
Keywords: Corporate Reputation Quotient; Brand Loyalty; Kurumsal İtibar Katsayısı; Marka Sadakati